Pengalaman Siswa Terhadap Pengaruh Lingkungan Sekolah dalam Memotivasi Belajar - Manda, Darman; Darmayanti, Dyan Paramitha (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the influence of the school environment on student learning motivation at SDN A Makassar. The focus of this study is to determine how the physical condition of the school environment, social atmosphere, and emotional support from teachers and peers contribute to increasing student learning motivation. The method used is qualitative interviews with students and teachers at the school. The results indicate that physical facilities, including comfortable classrooms, adequate learning materials, and spacious sports fields, have a positive impact on students' comfort and motivation in learning. Additionally, a positive social atmosphere, characterized by good relationships between teachers and students, as well as among peers, plays a crucial role in enhancing student motivation to learn. However, issues related to classroom cleanliness and facility maintenance are still factors that hinder student comfort. This study suggests that schools should improve physical facilities, enhance classroom cleanliness, strengthen social relationships between students and teachers, and increase parental involvement in the learning process. These findings are expected to serve as a reference for developing a school environment that is more conducive to student learning motivation.